2021
DOI: 10.1088/1755-1315/842/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Managing and protecting of endangered Rafflesia species in Kelantan, Peninsular Malaysia

Abstract: Rafflesia is the most magnificent and largest flower in the world. In Southeast Asia, the species becoming endangered due to anthropogenic activities such as logging, conversion of forest into large-scale agricultural areas, urbanization and unsustainable ecotourism. This paper has specifically highlighted the efforts that have been taken by the Kelantan State Forestry Department (KFD) in ensuring the sustainability and survival of this gigantic flower in its natural habitat. A survey by Universiti Malaysia Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Ex-situ conservation of R. zollingeriana is strongly suggested due to the severe external threat in the habitat. The presence of Rafflesia in ex-situ conservation areas is expected to be a solution to the difficulty of accessing Rafflesia insitu for research (Tolod et al, 2021;Lestari & Rianto, 2017) and the lack of a large enough population to be observed regularly (Fauzan et al, 2021). Ex-situ conservation of Rafflesia is also expected to help with the provision of knowledge and data about the species, which is still scarce and shrouded in mystery.…”
Section: Conservation Strategy Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex-situ conservation of R. zollingeriana is strongly suggested due to the severe external threat in the habitat. The presence of Rafflesia in ex-situ conservation areas is expected to be a solution to the difficulty of accessing Rafflesia insitu for research (Tolod et al, 2021;Lestari & Rianto, 2017) and the lack of a large enough population to be observed regularly (Fauzan et al, 2021). Ex-situ conservation of Rafflesia is also expected to help with the provision of knowledge and data about the species, which is still scarce and shrouded in mystery.…”
Section: Conservation Strategy Recommendationmentioning
confidence: 99%
“…All species of Rafflesia are endangered due to their biological (Hidayati & Walck, 2016) and ecological characteristics (Lestari et al, 2014b;Susatya et al, 2017). Anthropogenic activities such as knobs exploitation (Fatmawati et al, 2018), illegal logging, the conversion of forest into large-scale agricultural uses, urbanization, and mass ecotourism put an additional threat to their extinctions (Fauzan et al, 2021;Wicaksono et al, (2016). Despite they are all endangered species, their biological and ecological attributes are unfortunately rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Basor, and the Lojing Highlands [6,2]. According to various data reports, Lojing Highlands is a well-known location with the most R. kerrii population in Peninsular Malaysia [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%